2020
DOI: 10.3389/fnmol.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Treadmill Training Enhances Brain-Specific MicroRNA-34a in the Mouse Hippocampus

Abstract: Background: An imbalance between total training load and total recovery may cause overtraining (OT). The purpose of the present study was to verify the effects of OT on the expression of brain-derived neurotrophic factor (BDNF), its receptor tropomyosin receptor kinase B (TrkB) and p75 and the dynamic expression patterns of brainspecific miR-34a and miR-124 or inflammation-related miR-21 and miR-132 in the mouse hippocampus.Method: Eight weeks old C57BL/6J mice were randomly assigned to the control (CON), norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Exercise consisted of 2 weeks on a horizontal treadmill (5 days/week, 30 min/day, up to a speed of 30 cm/s) plus 2 days of recovery required for reducing animal stress, according to previous reports, 24 starting at 12 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise consisted of 2 weeks on a horizontal treadmill (5 days/week, 30 min/day, up to a speed of 30 cm/s) plus 2 days of recovery required for reducing animal stress, according to previous reports, 24 starting at 12 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise increases the release of BDNF from the human brain [ 231 , 232 ] suggesting that exercise also mediates central BDNF production in humans. It has been suggested that miR-34a potentially can also mediate changes in BDNF expression and may reflect the decrease in performance after overtraining [ 233 ].…”
Section: Neuroplasticity In Mdd: the Effects Of Antidepressant Thementioning
confidence: 99%
“…Although Feter et al, 2019 reported that interventions lasting at least 12 weeks with a session duration of 40 min would be the most prominent strategy for increasing BDNF levels in healthy or unhealthy adults (Feter et al, 2019). In contrast, overtraining seems to reduce BDNF level, but upregulates its receptors of "p75" and tropomyosin receptor kinase B (TRKB), in intact mice (Xu et al, 2020). Therefore, BDNF releasing system keeps enough sensitivity to be elevated, whenever encountering the different forms of exercise training, although acute exercising is more prominent.…”
Section: Brain Derived Neurotropic Factormentioning
confidence: 99%